2020
DOI: 10.9734/irjpac/2020/v21i330159
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis of Silver Nanoparticles Using Tri-sodium Citrate, Stability Study and Their Characterization

Abstract: The present work was aimed to study the synthesis of silver nanoparticles (Ag NPs) using Tri-Sodium Citrate (TSC), stability study of synthesized Ag NPs and their characterization. Synthesis of Ag NPs has been carried out by maintaining different conditions such as TSC concentration (0.50, 1.00 and 1.50%), AgNO3 concentration (0.50, 1.00 and 1.50 mM) and stirring time (10, 15 and 20 min). The stability study of synthesized Ag NPs conducted for 30 days without adding any stabilizing agents. The characterization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 13 publications
7
31
0
1
Order By: Relevance
“…The results of the synthesis revealed a spherical shape AgNP for the concentration of 1.5M with average size ranges between 19 and 32 nm. This finding conforms with a similar study that employed TSC as a reducing and stabilizing agent for the synthesis of AgNP ( Yerragopu et al., 2020 ). Although, the toxicity profile of AgNPs have been documented but they were mostly dependent on the concentration, size, duration, shape and pH of the medium ( Siddiqi et al., 2018 ).…”
Section: Discussionsupporting
confidence: 93%
“…The results of the synthesis revealed a spherical shape AgNP for the concentration of 1.5M with average size ranges between 19 and 32 nm. This finding conforms with a similar study that employed TSC as a reducing and stabilizing agent for the synthesis of AgNP ( Yerragopu et al., 2020 ). Although, the toxicity profile of AgNPs have been documented but they were mostly dependent on the concentration, size, duration, shape and pH of the medium ( Siddiqi et al., 2018 ).…”
Section: Discussionsupporting
confidence: 93%
“…Those four main peaks were present at 2 θ = 38:3 °, 44.49 °, 64.6 °, and 77.5 °that corresponds to Ag planes 111, 200, 220, and 311, respectively (Figure 7). FCC crystalline shape was previously reported in silver nanoparticle synthesis using various plant extracts as well as trisodium citrate as the chemical approach [19,[42][43][44] 8 shows differences between each synthesized AgNP with its reference. Any change in sharpness or position of any peak is referred to group contribution in silver nanoparticles' synthesis.…”
Section: Scanning Electron Microscope (Sem) and Xrdmentioning
confidence: 88%
“…Our formulated HAART-AgNPs revealed a spherical shape and mean nanoparticle sizes between 19 and 32 nm in all concentrations. Spherical shapes with nanoparticle size between 20 and 50 nm of nanoparticles have been described as not toxic to the biological tissue [44][45][46]. The previous literature has reported that size and shape are the primary determinants of toxicity in silver nanoparticles [47].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the toxicity criteria as reported in the literature ( [44][45][46]) such as particle size and shape, elemental compositions of this presence conjugated HAART-AgNPs with 1.5 concentration were used for animal studies.…”
Section: Discussionmentioning
confidence: 99%